PERAN PENDIDIK KRISTEN DALAM MEMANAJEMEN PENDIDIKAN AGAMA KRISTEN BAGI MAHASISWA YANG BERKEBUTUHAN KHUSUS DI STT DIAKONIS - Maranatha, Nathan Setya Adi (STT Kingdom, 2024)
Every individual has the right to receive education, including children with special needs (ABK), as God sees that every human being is valuable, so the same way of seeing and becomes the motivation of the Church, especially educators, to serve ABK by interpreting the existence of ABK in The class is God's call through educators to serve them. Educators need to play their role in managing Christian religious education for students with special needs, so that their right to education is fulfilled. This research uses literature methods. This research aims to provide a theoretical contribution regarding strategies or roles that can be maximized by Christian educators in managing Christian religious education for children/students with special needs